(3TQM WGT cHQi RGOIs - (3GdJQcj, CHh GdNjQ, WGTcHQj RGOg, YUGe GdOjf, CMeO Hf eUWai Hf Ndjd, (B968 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj dG eGfY dYWGFgabO cfJ cJHJ YOI ef GdSWhQ eY bdI GdHVGYI hcKQI GdaJhQ aj Yde GdefGVQI hGdBOGH hbO bUOJ TQMgG HYhf Gddg Gdedc GdhgGH , CMeOc Gddge jG eLjH s
(3BNQgG (B:s
(3hfhbT gPG GdJYQja HYOe UObg Ydi GdeGfY efYG eLQOG EP djS dg fXQ aj GdfSHI ajLGH Yfg HCf GdefY eVhJ dEKHGJ GdfSHI ajchf ef bHjd GdfXQ ajgG hdcd ef GdLGfHjf hVGFa s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\257s
(3cTa GdXfhf (B1/41s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs